Suicidal behaviors among refugee women in Jordan: post-traumatic stress disorder, social support and post-displacement stressors - Mohamad Adam Brooks; Anindita Dasgupta; Maysa' Khadra; Ahmad Bawaneh; Neeraj Kaushal; Nabila El-Bassel (BMC, 2024)
Abstract Background This paper examines the frequency of suicidal behaviors (suicidal ideation or attempt) among a sample of Syrian refugee women living in non-camp settings in Jordan. We asked several questions surrounding suicide and examined the associations between post-traumatic stress disorder (PTSD), social connectedness, post-displacement stressors and suicidal behaviors. Methods Participants (n = 507) were recruited using a clinic-based systematic sampling from four health clinics throughout Jordan in 2018. We used a multivariable logistic regression to examine the hypothesis of whether positive screening for PTSD (PCL-5), social isolation (have no friends or family members available to help), and greater number of post-displacement stressors (PMLD Checklist) is associated with suicidal behaviors. Results Approximately one-tenth (9.86%) of participants surveyed reported suicidal behaviors (suicidal ideation or attempt) in the past six months. Our hypothesis was partially supported. In the adjusted multivariable analyses, screening positive for PTSD [OR:4.02 (95% CI:1.33, 12.15)] increased odds of suicidal behaviors, while having one friend or family member available to help when in need [OR:0.31 (95% CI:0.13, 0.78)] decreased odds of suicidal behaviors. We did not find any associations between the number of post-displacement stressors and suicidal behaviors in the multivariable model. Conclusion Agencies and practitioners addressing suicidal behaviors among Syrian refugee women should provide interventions that aim to reduce PTSD symptoms and social isolation. Potential intervention includes screening for mental health symptoms and suicidal behaviors during routine visits with service providers, as well as providing proper mental health and psychosocial support services according to the mapping of available services.